2018
DOI: 10.1016/j.micromeso.2017.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Using double pulsed-field gradient MRI to study tissue microstructure in traumatic brain injury (TBI)

Abstract: Double pulsed-field gradient (dPFG) MRI is proposed as a new sensitive tool to detect and characterize tissue microstructure following diffuse axonal injury. In this study dPFG MRI was used to estimate apparent mean axon diameter in a diffuse axonal injury animal model and in healthy fixed mouse brain. Histological analysis was used to verify the presence of the injury detected by MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(86 citation statements)
references
References 22 publications
2
83
1
Order By: Relevance
“…Peaks were observed in the distributions at 2 and 5 μm ID, in agreement with the expected nominal diameters of the taxon fibers contained within the micro-phantoms. A second peak in the distribution at 11 μm was thought to reflect the interstitial fluid compartment surrounding the taxons ( Komlosh et al, 2018 ). The results demonstrate the benefits of synthetic, biomimetic phantoms in gaining parametric control over taxon diameters, packing density and orientation, which will be leveraged for systematic multi-scale validation of diffusion microstructural metrics obtained on the next-generation Connectome system.…”
Section: Multi-scale Validation Of Microstructural Measures In Biomim...mentioning
confidence: 99%
“…Peaks were observed in the distributions at 2 and 5 μm ID, in agreement with the expected nominal diameters of the taxon fibers contained within the micro-phantoms. A second peak in the distribution at 11 μm was thought to reflect the interstitial fluid compartment surrounding the taxons ( Komlosh et al, 2018 ). The results demonstrate the benefits of synthetic, biomimetic phantoms in gaining parametric control over taxon diameters, packing density and orientation, which will be leveraged for systematic multi-scale validation of diffusion microstructural metrics obtained on the next-generation Connectome system.…”
Section: Multi-scale Validation Of Microstructural Measures In Biomim...mentioning
confidence: 99%
“…The randomly oriented phantom data were acquired dPFG parameters were as follows tau m = 0 or 6 ms; δ = 3 ms; ∆ = 30 ms; Three shells of 7, 16, and 37 directions with q ranging from 0 to 8.5947 x10 4 m −1 . For the tau m = 0 experiment the angles describing the gradient directions and the shell number were varied using a previously published 3D acquisition scheme [30]. For the long tau m acquisition each direction was applied with ϕ = 0 and 180 degrees.…”
Section: Double Pulse Field Gradient Mrimentioning
confidence: 99%
“…A simulation study nicely showed that the DDE technique is highly applicable to the diseased CNS, since DDE‐derived indices performed better than DTI indices for complex and coherently arranged fibers, and to fibers simulated to have a beaded structure consistent with injury (Skinner, Kurpad, Schmit, & Budde, 2015). The technique has also been applied to the brain (Jespersen et al, 2013), and has recently been shown to be useful for detecting increases in apparent mean diameter of axons in the optic tract after brain injury in the mouse (Komlosh et al, 2018), and for predicting functional and histological outcome after spinal cord injury in rodents (Skinner et al, 2018).…”
Section: Balancing Acquisition Time Versus Structural Informationmentioning
confidence: 99%